International Media Assistance: Experiences and Prospects - Myers, Mary; Dietz, Christoph; Frère, Marie-Soleil (Global Media Journal - German Edition, 2015)
As an introduction to this special issue this article deals firstly with defining and clarifying terms and concepts which are used in the context of international media assistance. Secondly, the themes of the different articles in this collection are enumerated: these are broadly the how to of media assistance, evaluation and the ongoing debate about proving impact of media assistance project; negotiating the tensions between the state and the media and finally, the fundamental question of why and to what purpose is assistance to the media sector given in the first place. The first two of these themes are developed in slightly more depth. The piece is rounded off with some further reflections on the history both of the idea of media assistance and of the way it has been practiced in recent decades. It finally looks at the ways research in this field may develop in the future.